2021
DOI: 10.1186/s40104-020-00521-7
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with sodium butyrate improves growth and antioxidant function in dairy calves before weaning

Abstract: Background There is increasing research interest in using short-chain fatty acids (SCFAs) including butyrate as potential alternatives to antibiotic growth promoters in animal production. This study was conducted to evaluate the effects of supplementation of sodium butyrate (SB) in liquid feeds (milk, milk replacer, and the mixture of both) on the growth performance, rumen fermentation, and serum antioxidant capacity and immunoglobins in dairy calves before weaning. Forty healthy female Holstei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 48 publications
5
19
0
Order By: Relevance
“…Maternal supply of RPAA plays an important role and can have an effect on the immune system in newborn calves, as indicated by the higher concentration of serum Brix and IgG in claves conceived from supplemental-AA cows in the current study. These results similar to previous studies reported that pre-calving supply of RPM can influence immune function in the neonatal calf ( 11 13 ); three important antibodies of the immune system, IgA, IgG, and IgM, protect humans and animals, including calves, against many kinds of pathogens and viruses, activate the complement system, regulate antibody-dependent cell-mediated cytotoxicity, and improve immunity ( 46 , 47 ). In addition, methyl-donors also act as anti-inflammatory regulators in ruminants, as increased methyl-donor (e.g., Met, betaine, choline, folate, and B12) supply in cows during the transition ( 48 ), and late gestation periods ( 12 ), leads to decreased haptoglobin, a biomarker used to predict disease.…”
Section: Discussionsupporting
confidence: 91%
“…Maternal supply of RPAA plays an important role and can have an effect on the immune system in newborn calves, as indicated by the higher concentration of serum Brix and IgG in claves conceived from supplemental-AA cows in the current study. These results similar to previous studies reported that pre-calving supply of RPM can influence immune function in the neonatal calf ( 11 13 ); three important antibodies of the immune system, IgA, IgG, and IgM, protect humans and animals, including calves, against many kinds of pathogens and viruses, activate the complement system, regulate antibody-dependent cell-mediated cytotoxicity, and improve immunity ( 46 , 47 ). In addition, methyl-donors also act as anti-inflammatory regulators in ruminants, as increased methyl-donor (e.g., Met, betaine, choline, folate, and B12) supply in cows during the transition ( 48 ), and late gestation periods ( 12 ), leads to decreased haptoglobin, a biomarker used to predict disease.…”
Section: Discussionsupporting
confidence: 91%
“…Oxidative stress (OS), considered to be a state of imbalance between antioxidation and oxidation, can seriously debase the productivity and even lead to animal death [ 47 ]. Investigations have shown that SB can improve the antioxidant capacity and protect against OS damage on animals [ 14 , 48 , 49 ]. The intestine is highly susceptible to OS, which causes the waste of nutrients as well as gut dysfunction and body disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium butyrate (SB) is a common feed additive. Previous studies have shown that dietary sodium butyrate supplementation can improve animal immune responses (5) and growth performance (6,7). However, birds are reluctant to eat SB due to its unappetizing smell and therefore its digestibility decreases (8).…”
Section: Introductionmentioning
confidence: 99%